(untitled) (LEGAL DIALOGICA, 2025)
This study aims to identify the effectiveness of rehabilitation programs for narcotics users in preventing the recurrence of narcotics crimes. The background of this research is based on the increasing number of recidivist narcotics cases and the importance of a comprehensive recovery approach. This study uses a normative-empirical legal method with a qualitative approach, through literature studies and interviews at the Rehabilitation Center of the National Narcotics Agency Baddoka Makassar. The results of the study show that the regulation of rehabilitation of narcotics users has been comprehensively prepared in terms of law and implementation, but in the post-rehabilitation aspect it still shows legal weaknesses. And the effectiveness of Rehabilitation still faces challenges such as lack of family support, weak follow-up monitoring and most importantly the influence of an unsupportive social environment. These factors cause some clients to return to abusing narcotics. In addition, there are still limitations in the evaluation system and service integration between sectors. This study concludes that the effectiveness of rehabilitation is highly dependent on the sustainability of structured post-rehabilitation assistance programs and the active participation of families and communities. There is a need to increase cross-sectoral cooperation, local community involvement, and strengthen vocational and psychosocial programs for former narcotics users. With a more humane and comprehensive approach, rehabilitation can be a solution to break the cycle of addiction and narcotics crimes.. Abstrak: Penelitian ini bertujuan untuk mengidentifikasi efektivitas program rehabilitasi terhadap pengguna narkotika dalam mencegah terjadinya pengulangan tindak pidana narkotika. Latar belakang penelitian ini didasari oleh meningkatnya jumlah residivis kasus narkotika serta pentingnya pendekatan pemulihan secara menyeluruh. Penelitian ini menggunakan metode hukum normatif-empiris dengan pendekatan kualitatif, melalui studi pustaka dan wawancara di Balai Rehabilitasi Badan Narkotika Nasional Baddoka Makassar. Hasil penelitian menunjukkan bahwa pengaturan rehabilitasi pengguna narkotika telah disusun secara menyeluruh dari sisi hukum dan pelaksanaannya, namun dalam aspek pascarehabilitasi masih menunjukkan kelemahan hukum. Serta efektivitas Rehabilitasi masih menghadapi tantangan seperti, kurangnya dukungan keluarga, lemahnya pemantauan lanjutan dan yang paling penting adalah pengaruh lingkungan sosial yang tidak mendukung. Faktor-faktor ini menyebabkan sebagian klien kembali melakukan penyalahgunaan narkotika. Selain itu, masih ditemukan keterbatasan dalam sistem evaluasi dan integrasi layanan antar sektor. Penelitian ini menyimpulkan bahwa efektivitas rehabilitasi sangat bergantung pada keberlanjutan program pendampingan pascarehabilitasi yang terstruktur dan partisipasi aktif keluarga serta masyarakat. Diperlukan peningkatan kerja sama lintas sektor, pelibatan komunitas lokal, serta penguatan program vokasional dan psikososial bagi mantan pengguna narkotika. Dengan pendekatan yang lebih manusiawi dan komprehensif, rehabilitasi dapat menjadi solusi untuk memutus siklus kecanduan dan tindak pidana narkotika.